Power-to-strength ratio influences performance enhancement with contrast training - Schneiker, K. T.; Fyfe, J. J.; Billaut, F.; Bishop, D. J. (Medicine & Science in Sports & Exercise, 2018)
Purpose The effectiveness of contrast training (CST) for improving explosive exercise performance is modulated by various individual characteristics; however, further work is required to define these factors. Methods Subelite male Australian Football players (n = 22; age, 19 ± 2 yr; body mass, 80.4 ± 9.4 kg; one-repetition maximum [1-RM] half squat, 172 ± 18 kg; mean ± SD) completed two experimental trials involving two sets of squat jumps (six repetitions at 30% 1-RM) performed either alone (CTL condition) or after half squats (six repetitions at 85% 1-RM; CST condition). Results Squat jump peak power was similar between CTL and CST during set 1 (mean change: ±90% confidence interval, 2.8% ± 2.0%; effect size [ES]: ±90% confidence interval, 0.13 ± 0.09; P = 0.079) and set 2 (0.3% ± 1.7%; ES, 0.01 ± 0.08; P = 0.781). Peak power enhancement with CST was not related to maximal (1-RM half squat) strength (r 2 = 0.001, P = 0.884), but was negatively correlated with both baseline peak power (r 2 = 0.44, P < 0.001) and power-to-strength ratio (PSR); that is, the ratio between baseline peak power and 1-RM half squat strength (r 2 = 0.65, P < 0.001). Using a median split, analyses were performed in participants with a low PSR (LPSR group; PSR = 15.4-19.1 W/kg; n = 11) or high PSR (HPSR group, PSR = 19.4-24.7 W/kg; n = 11). Peak power was enhanced with CST for the LPSR (8.1% ± 3.9%; ES, 0.44 ± 0.21; P = 0.004) but not HPSR (-2.1% ± 1.3%; ES, -0.14 ± 0.09; P = 0.010) groups. Conclusion The PSR appears to influence the effectiveness of CST, with performance enhancement more likely in those with a lower PSR.